PENGUKURAN KINERJA PERGURUAN TINGGI (STUDI PADA FKIP UNIVERSITAS LAMBUNG MANGKURAT) - Maulana Rizky (ABIS: Accounting and Business Information Systems Journal, 2013)
Reform became a milestone of institutional and bureaucratic order of life in Indonesia, where all stakeholders started demanding the delivery of good governance of public sector organizations. Performance measurement into one of the tools to realize the management of public sector organizations based on principles of good governanceThis study aims to determine the achievement of the performance of a faculty State University (PTN), namely the Faculty of Teacher Training and Education (FKIP) Lambung Mangkurat University. Performance measurement at the FKIP Lambung Mangkurat University using variable financial performance, the performance of community service, educational performance and teaching, and research performance. In addition, to determine whether FKIP UNLAM has a planning tool or program evaluationThis study uses a mixed (mixed method). This method consists of two phases, namely the first phase of quantitative or hypotheses and then continued the second phase is the qualitative phase to strengthen the hypothesis test results. Quantitative methods using Structural Equation Models (SEM) with a variance approach, followed by using a qualitative method of thematic content analysis of interviews to the respondents.The results showed that all the variables of financial performance, the performance of community service, educational performance and teaching, and research performance has an influence on organizational performance FKIP UNLAM. Education and teaching performance has a very high influence, while the performance of research has least influence than 3 (three) other performance. Based on the research also showed that organizational performance is influenced by the Institutional Theory.